HUBUNGAN PENGALAMAN, KEYAKINAN, UMUR SERTA PERAN TEMAN SEBAYA DENGAN KEMAMPUAN IBU PRIMIPARA DALAM PERAWATAN BAYI BARU LAHIR DIRUMAH - ULVA NOVIANA; Heni Ekawati (NHM PRESS, 2021)
Baby care is an action taken to care for and maintain the healt of the baby,as well as fulfill the basic needs of the baby. Based on the results of the preliminary study conducted at BPS Luk Luatun Mubrikoh S.ST. On December 10th,2018 on 10 postpartum mother there were 4 postpartum mother (40%) who lacked the ability to care for newborns.The purpose of the study is to determine the factors correlations with care of newborns.This study was an analytical study with a cross sectional approach. Independent variables of this study were experiences,beliefs,ages,peers role, dependent variable was the ability of newborns care. The study population were 47 postpartum mothers and the samples taken were 42 postpartum mothers with purposive sampling technique. Data collection using a questionnaire. The result of the study were tabulated and then bivariate analysis was performed with the spearman rank statistical test α (0,05). This reaserch has carried out ethical clearance test by the KEPK of the STIKes Ngudia Husada Madura.The results showed that most (54.8%) postpartum mothers had sufficient experience, half (50,0%) mothers had moderate confidence, half the age of early adult mothers (50.0%) the majority (61,9%) mother have sufficient peer roles, half (50,0%) of the ability to care for newborns was good. The results of the study used Spearman rank (ρ=0.006<α=0.05), (ρ=0.007<α=0.05) ,(ρ=0.002<α=0.05) and (ρ=0.003<α=0.05), meaning that there was a relationship between experience,belief,ages and peer role with the ability to care for newborns. Based on the results of this studyit is expected that health workers provide counseling about neborn care and convincing ways to prepare for the role being a mother for the age of marriage should be above 20 years, this aims to improve the ability of newborn care at home